2007
DOI: 10.1158/0008-5472.can-06-4066
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin-Cleaved COOH-Terminal Osteopontin Peptide Binds with Cyclophilin C to CD147 in Murine Breast Cancer Cells

Abstract: Osteopontin is a glycoprotein that has been linked to metastatic function in breast, lung, and prostate cancers. However, the mechanism by which osteopontin acts to induce metastatic properties is largely unknown. One intriguing feature of osteopontin is the presence of a conserved thrombin cleavage site that is COOH-terminal from a well-characterized RGD domain. Although the COOH-terminal fragment may bind to cell surface CD44 receptors, little is known about the COOH-terminal osteopontin fragment. In the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 24 publications
2
47
0
Order By: Relevance
“…First, the parent proteins listed are not functionally exclusive to coagulation or fibrinolysis. This observation is consistent with previous studies, where a thrombin is implicated as a proteolytic agent in other biological processes (30)(31)(32). Second, only a very few of the cleavage sites match the R-G motif commonly expected for a thrombin, and there are a few missed R-G sites included in the observed peptides.…”
Section: Variability Of Serum Protein and Peptide Contentsupporting
confidence: 92%
See 1 more Smart Citation
“…First, the parent proteins listed are not functionally exclusive to coagulation or fibrinolysis. This observation is consistent with previous studies, where a thrombin is implicated as a proteolytic agent in other biological processes (30)(31)(32). Second, only a very few of the cleavage sites match the R-G motif commonly expected for a thrombin, and there are a few missed R-G sites included in the observed peptides.…”
Section: Variability Of Serum Protein and Peptide Contentsupporting
confidence: 92%
“…Enzymes in the clotting cascade, though specific in biological role, have been shown to have promiscuous activity (4,5,(30)(31)(32), outside their expected catalytic function. The data presented here provide direct evidence of this substrate promiscuity, acting broadly upon the protein and peptide content of the plasma/serum itself.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in the present study, interference with Basigin expression suppressed the proliferative potential of GC cells in vitro. In agreement with a recently published study (17,18), we found up-regulated expression of Basigin mRNA in GC cells, suggesting its participation in the process of proliferation as an essential component of cell surface signaling transduction. Li et al (19) and Xu and Hemler (20) showed a strong association between cell proliferation and the Basigin-CD98 cell surface super complex, which plays a critical role in energy metabolism.…”
Section: Discussionsupporting
confidence: 93%
“…However, its mechanism of action is unknown. OPN was previously shown to promote tumor adhesion and metastasis, potentially through direct binding to integrins and regulation of epidermal growth factor receptor and hepatocyte growth factor receptor (17,(28)(29)(30)(31)(32). These findings and our observations from a previous study (15) prompted us to hypothesize that OPN is critically involved in leukocyte migration and perpetuation of synovitis in RA.…”
Section: Discussionmentioning
confidence: 59%